Urdu Tadreesi Muawnaat Miyad Dom KG (Lahore The City School)
A comprehensive resource pack designed to support Urdu language teaching for KG students during Term 2.
Educational material for KG level, Term 2
For Kindergarten students
Keywords: Urdu language - Study and teaching (Preschool)-Early childhood education - Pakistan